Omics in laboratory medicine. (19th September 2013) - Castaldo, Giuseppe; Scorza, Manuela; Elce, Ausilia; Giordano, Sonia; Liguori, Renato; Guerra, Germano
Abstract: In the last years, molecular diagnosis of human genetic diseases has greatly improved thanks to the knowledge of more than 7, 000 disease genes (genomics). However, the study of such diseases revealed the very complex relationships between the phenotype of each disease and the molecular alterations responsible. The analysis of proteins (proteomics) revealed that most proteins are subjected to post-translational changes or to alternative splicing; the study of gene expression identified a series of mechanisms that modulate gene expression (epigenomics) which include microRNA regulation, histone acetylation and gene methylation. The alteration of all these mechanisms may contribute to the pathogenesis or to the phenotypic expression of most human genetic diseases. Molecular analysis became more and more complex, but "omics" studies revealed that each single individual is "unique".